The level of political efficacy among senior citizens in selected barangays in Jaro, Leyte. - Celis, Annel Ruth, et al; Nebrida, Leoniza Frances P. (Annel Ruth Celis, 2010)
Jaro is a fourth class municipality in the Province of Leyte. The researches were interested in finding out the degree to which senior citizens of the said municipality perceived their own level of political efficacy. Political efficacy which refers to the feeling that political and social change is possible and that the individual citizen can play a part in bringing about this change, is composed of internal and external political efficacy. Internal political efficacy is the confidence of the individual in his or her own abilities to understand politics and to act politically. External political efficacy is the individual's belief in the responsiveness of the political system.